Research on travel time prediction of expressway in peak period based on Greenberg model. (5th April 2023) - Xing, Yan; Hao, Yuqing
Expressway travel time is an important parameter to describe the traffic status, which can accurately reflect the efficiency of expressway traffic. To further simplify the complexity of the travel time prediction method, and improve the prediction accuracy, in this paper, the travel time prediction of the expressway is divided into three cases for discussion. First of all, based on the Greenberg model, under the premise of a comprehensive analysis of the section flow, traffic density, and other factors, to establish different sections under the peak period expressway vehicle travel time prediction model. Finally, the model is verified by taking the expressway around the city as an example. The results shows that the prediction results are always within 10% of the actual measurement error, which shows that compared with the measured data, the error of the model proposed is small, the prediction accuracy is high, within the acceptable range.